2015
DOI: 10.1108/rsr-07-2015-0036
|View full text |Cite
|
Sign up to set email alerts
|

Writing a research paper: students explain their process

Abstract: Purpose-This study aims to explore how students conceptualize the research process, describing in their own words the strategies they used, as well as the successes and challenges they encountered. Areas of review include: thesis definition; search strategies; quality, variety and depth of resources; and source evaluation and citation. Design/methodology/approach-The study analyzes 76 essays written by undergraduate and graduate students, describing their research process. Quotations from the students' essays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…The learning process or the results as evaluation is used by teachers to gather information, analyze and interpret it, infer, make wise decisions and take appropriate actions in the service of improving teaching and learning (Berry, 2008). Students realize that the more specific they understand the lesson the better the results are obtained (Dubicki, 2015). The implementation of learning is the identification of students' needs, the application of the learning programs, the assessment of the process and the results and impacts of which there is a learning experience that students obtain (Katiah, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The learning process or the results as evaluation is used by teachers to gather information, analyze and interpret it, infer, make wise decisions and take appropriate actions in the service of improving teaching and learning (Berry, 2008). Students realize that the more specific they understand the lesson the better the results are obtained (Dubicki, 2015). The implementation of learning is the identification of students' needs, the application of the learning programs, the assessment of the process and the results and impacts of which there is a learning experience that students obtain (Katiah, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The professor, TA, and librarian agreed that for future iterations students would need a more concrete opportunity to practice their academic research skills-perhaps through a combination of their "Personal Research Profile" and a wellscaffolded annotated bibliography. The annotated bibliography is not a particularly fresh idea, but students have remarked on its value in exploring different perspectives (Dubicki, 2015). Students could also write a group paper, contribute to a student-based academic journal, publish Wikipedia articles, develop a podcast, or work together to address a "wicked" problem, whether it be social, environmental or other.…”
Section: What About Practical Application?mentioning
confidence: 99%
“…Although scholars have a difficult time proving causality, they accept that there is a correlational relationship between library instruction and certain student success measures (Wong & Webb, 2011;Bowles-Terry, 2012;Badke, 2014). Researchers have found that students affirm information literacy helps them with their coursework and day to day lives (Detlor et al, 2012;Dubicki, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Although the argument has not been settled, researchers have reported that information literacy instruction, in general, has a positive impact on student success (Eng & Stadler, 2015;Cook 2014). The research literature also suggests students feel better prepared for college when given library instruction (Dubicki, 2015).…”
Section: Information Literacy Instruction's Impact On College Studentsmentioning
confidence: 99%
See 1 more Smart Citation